Computers in Cardiology 1997
DOI: 10.1109/cic.1997.648135
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Netherlands pacemaker patient registry

Abstract: This paper deals with the validation of the information stored in the Netherlands central pacemaker patient database. At this moment the registry database contains information on more than 70500 patients, 85000 pacemakers and 90000 leads. The validation procedures consisted of an internal consistency check and comparison with different hospital and pacemaker company databases. Although comparison of the exact information resulted in a meager agreement, the relevant information, based on the purpose of the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, some may have been overlooked due to unavailability of highly detailed patient-related data needed to distinguish duplicate records. Nevertheless, 99 % of all implantations are registered [12, 18] and the data provide useful information; therefore, errors are expected to be random with regard to indication and pacemaker properties. In contrast to the ECG data and symptoms, information on aetiology is absent in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some may have been overlooked due to unavailability of highly detailed patient-related data needed to distinguish duplicate records. Nevertheless, 99 % of all implantations are registered [12, 18] and the data provide useful information; therefore, errors are expected to be random with regard to indication and pacemaker properties. In contrast to the ECG data and symptoms, information on aetiology is absent in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the data were periodically returned to the clinics for correction purposes. A validation process in order to obtain better insight into the quality of the database was performed in 1997 [12]. …”
Section: Methodsmentioning
confidence: 99%
“…A validation process to obtain better insight into the quality of the database was performed in 1997. A total of 84.0% of the sold leads could be retrieved in the central registry when compared to patient files of participating hospitals and sales data from manufacturers …”
Section: Methodsmentioning
confidence: 99%
“…To identify CIED failures, a registry was set up in the Netherlands in the early 1980s: the Central Pacemaker Patients Registration (CPPR) from the Netherlands Pacemaker Registry Foundation (CPPR‐SPRN) . This registry collected data over 25 years and allows for analysis of trends over time regarding the duration of service time or longevity of leads after first implantation .…”
Section: Introductionmentioning
confidence: 99%
“…A validation study in 1997 showed that more then 95% of pacemaker implantations in the Netherlands were correctly recorded in the CPPR. 3 Since 1990 the ICD registration was added to the registration, ending in 2007 with a total of 14,131 implantations. Also the database contained information on 1600 pacemakers and ICD models, and 1900 lead models that were implanted in this period.…”
Section: Resultsmentioning
confidence: 99%